Pengelolaan, Pemanfaatan, dan Pelestarian Hutan Mangroove Sebagai Wisata Religi di Desa Adat Sesetan, Denpasar - I Gusti Agung Ayu Gita Pritayanti Dinar; I Made Pria Dharsana; Kade Richa Mulyawati; I Kadek Wahyu Dwi Payana; Putu Marita Maharani Putri; Kadek Nadya Pramita Sari (Kertha Wicaksana, 2025)
The aim of this research is to find out local wisdom which has positive implications in improving the economy of local communities, to understand natural and cultural phenomena and provide support for the preservation of nature and culture itself so that the Balinese tourism format which is thick with cultural tourism will never fade. The cultural character and cultural heritage of Bali which includes symbols, signs, forms of written artistic expression, language, lifestyle, ritual systems, traditional knowledge and mythology inherited from the predecessors of the Balinese people make it a special attraction for the world of tourism. Tukad Rangde as a barrier between the Mangroove forest and Attack Island requires special attention to be developed and managed with appropriate methods for the preservation and sustainability of customs and culture in the context of implementing religious tourism and ecotourism in the Mangroove forest.  Therefore, the specific target of this research is to examine the collaborative arrangements for managing the use of Mangroove forest conservation in Sesetan village and to examine the development of the use of Mangroove forests for Hindu religious ritual facilities in Sesetan village.